Reduction of Antinutritional Factors in Cereal Brans for Product Development. Issue 3 (24th February 2014) - Kaur, Satinder; Dar, B.N.; Pathania, Shivani; Sharma, Savita
Abstract Different chemicals at varying concentrations were assessed to inactivate the antinutritional components in cereal brans. HCl (4%) used at 3, 4 and 5%; acetic acid (1%) used at 18, 20 and 22%; and calcium hydroxide (1%) used at 18, 20 and 22% were mixed with cereal brans. Maximum reduction in trypsin inhibitor followed by oxalates, polyphenols, phytic acid and saponins was achieved on treating with 1% acetic acid used at 22%. Acetic acid (1%) used at 22% was the most effective in reducing the antinutritional factors of cereal brans, followed by calcium hydroxide (1%) used at 22% and hydrochloric acid (4%) used at 5%. Besides affecting the antinutritional components, chemical treatments have shown profound effect on bulk density and color value of cereal brans. To explore the potential of cereal brans, bread and macaroni were prepared by substituting flour with cereal brans singly and in combination. The products were acceptable to consumers. Practical Applications Cereal brans, being a good source of vitamins and other nutrients, are underutilized as a functional food component. Effective processing (using chemicals) can result in a significant reduction in antinutrient components of the bran and will enhance the functionality of the bran. These processed brans can be utilized in the development of functional products as a fiber supplement. Hence, it can go a long way in supplying the required quantities of cheap and easily available dietary fiber and protein to various segments of our population and also results in profitable utilization of by‐products of milling industry.